THE IMPLEMENTATION OF HIGHER-ORDER THINKING SKILL (HOTS) IN LEARNING READING FOR EFL LEARNERS - Nurmaharaeni; Syamsiarna Nappu; Uyunnasirah Hambali (FKIP Unismuh Makassar, 2022)
This research aims at finding out the students’ reading comprehension ability after implementing HOTS in learning process and the differences between those who are taught by implementing HOTS and those who are not, especially in making inference.This quasi-experimental research using two groups, experimental and control group through pre-test and post-test results. The samples are 23 students from class VIIIC and 22 students from class VIIIB of SMP Negeri 1 Cina which are taken by using Purposive Sampling Technique. The data obtained are analyzed using SPSS Application version 25.The finding shows that the mean score of pre-test in experimental class is 48.04 and the post-test score is 71.09. While in control class, pre-test score is 48.42 and in post-test is 50.91. After implementing HOTS in the classroom, reading comprehension ability increases to 32.42% and 4.9% in control class. This finding indicates that HOTS brings good effect in learning reading comprehension process because students can get used to questions related to making inference and their ability to answer reading comprehension questions improves. Students be able to predict questions and provide logical reasons related to texts and learning materials. Then it can be concluded that there are differences between those who are taught by HOTS and those who are not, in terms of learning outcomes and also the way they think.